ChemInform Abstract: Rapid Wolff—Kishner Reductions in a Silicon Carbide Microreactor. Issue 18 (17th April 2014) - Newman, Stephen G.; Gu, Lei; Lesniak, Christoph; Victor, Georg; Meschke, Frank; Abahmane, Lahbib; Jensen, Klavs F.
Abstract: The reaction is performed in a novel silicon carbide microreactor.